Targeting p66Shc to restore KATP channel and renal microvascular responses in a preclinical model of diabetic nephropathy - Miller, Bradley; Imig, John; Goorani, Samaneh; Schupbach, Perrin; Hays, Franklin; Benbrook, Doris M.; Sorokin, Andrey (Frontiers in Physiology, 2025)
Renal microvascular injury occurs in most patients with diabetes, representing one of the main causes underlying chronic kidney disease development. We have previously published that overexpression of adaptor protein p66Shc is implicated in the loss of renal microvascular reactivity in rats with diabetic nephropathy (DN) induced by injection of streptozotocin (STZ). Since sulfur heteroarotinoid A2 (SHetA2) is known to interfere with p66Shc signaling, we tested whether SHetA2 would restore renal microvascular reactivity and mitigate kidney injury in our rat model of DN. Dahl salt sensitive wild-type (SS) and p66Shc knockout rats were used in a well-established rat model of DN, characterized by progressive proteinuria, hyperfiltration, and display of renal histological lesions. SHetA2 was either added acutely to isolated rat afferent arterioles or chronically administrated to rats during DN development. The ability of SHetA2 treatment to restore afferent arteriolar contraction in response to increased perfusion pressure or ATP was evaluated using the perfused juxtamedullary nephron preparation. The progression of renal damage was evaluated by measuring urinary protein excretion. Comparison of renal microvascular responses to perfusion pressure in p66Shc knockout rats and parental SS rats, in the presence and absence of acute preincubation with SHetA2, revealed ability of SHetA2 to restore renal microvascular reactivity in SS rats with little effect upon p66Shc knockouts. Moreover, chronic treatment with SHetA2 prevented loss of renal microvascular responses. Even though targeting p66Shc with SHetA2 restored renal afferent arteriolar reactivity caused by DN, it had limited effect upon a biomarker of renal injury. Thus, additional studies are necessary to develop SHetA2 for prevention and treatment of DN-induced kidney damage.